Multiple and solitary skeletal muscle metastases on 18F-FDG PET/CT imaging. Issue 11 (November 2015) - Nocuń, Anna; Chrapko, Beata
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to investigate the features and patterns of skeletal muscle metastases (SMM) detected with 18F-fluorodeoxyglucose (18F-FDG) PET/computed tomography (PET/CT). Participants and methods Our database was analyzed for patients with pathologically proven malignancy, who underwent 18F-FDG PET/CT in our institution. The patients with SMM were included in the study group on the basis of the final diagnosis confirmed by follow-up or histopathology. Images were acquired using a PET/CT system Biograph mCT S(64)-4R. CT was performed without contrast enhancement. Results The selected group included 31 patients (1.7% of the database, which consisted of 1805 patients). A total of 233 lesions were found. The prevalence of SMM evaluated in specific primary malignancies was the highest in melanoma (6.9%), followed by carcinoma of unknown primary (4.4%), colorectal cancer (4.1%) and lung cancer (2.8%). Three patterns of skeletal muscle metastatic involvement were observed: multiple SMM accompanied by other metastases (64.5%), solitary lesion associated with other metastases (29%) and isolated intramuscular lesions (two cases, 6.5%). Isolated SMM represented recurrence of the malignant disease. In patients with extraskeletal metastases, solitary or multiple SMM did not affect tumor staging. Conclusion Solitary SMM are less common than multiple on 18F-FDG PET/CT imaging. SMM are usually associated with other metastases and do not affect tumor staging. The cases of isolated SMM are very rare. Nevertheless, in patients with a diagnosis of malignant disease, a solitary, 18F-FDG avid intramuscular focus should be suspected to represent metastasis.